Violent Personal Crimes on Campus: The Influence of Size, Setting, and Police Presence - McKinney, Chris (2007)
Statement of the Problem Violent campus crime, in particular rape and aggravated assault, has become more pronounced in the last several decades. The judicial and legislative branches have responded through court decisions and legal enactments that require most universities to collect and report campus crime data. Many concerns have arisen as to the effectiveness and implications associated with such mandates. Some believe current laws do little to improve campus safety. Some suggested solutions to address campus crime have involved safety initiatives/programs and potential staffing increases to their campus police force. Research Questions Are universities a reflection of surrounding community levels on violent crime and police staffing? Are violent on campus crimes and police staffing impacted by university location and enrollment? Does a relationship exist between police staffing and violent levels of personal crime? Methodology This study used a population of all Kentucky state-sponsored universities and their surrounding communities. Study measures involved demographic characteristics, police presence and violent personal crime. The data were analyzed using SPSS descriptively, in terms of frequency and measures of central tendency, and inferentially to test hypotheses. Independent t-tests were used to test differences in dependent variables (police presence and prevalence of crime) between campus and community. Differences in dependent variables by institutional setting were computed using a series of one-way analysis of variance (ANOVA). Findings Steady growth in both enrollment and community population existed from 2002-2005. However, campus growth outpaced surrounding community growth. The staffing level for campus police was less than their host community counterparts, but proved statistically significant in only two study years. In spite of comparatively smaller campus police presence, the risk of aggravated assault was higher for community residents than students on campus. However, the prevalence of forcible rape did not differ between campuses and community for any of the years observed. While campus police officer to student ratios declined as campus enrollment increased, there were no statistically significant correlations between the prevalence of forcible rape and university enrollment. Limitations on the study include: the study’s small sample, which impacts statistical testing unless strong correlations are identified; the lack of statistical significance for prevalence of forcible rape by both university and host community size should be interpreted cautiously because of the small cell sizes within each level; data reporting limitations, where discrepancies were identified and addressed; and other factors such as misreporting/underreporting also served as limitations but can not be fully properly measured. Recommendations The following recommendations are suggested: 1) further research needs to be conducted to measure factors not captured in this study, 2) an increase in campus police may result in potential on campus assault reduction, but have little impact reducing on campus rape –meaning additional and comparative program evaluations should be undertaken to measure the effectiveness of other campus safety initiatives, 3) to make campuses safer and to reduce institutional liability – administrators must continue to develop and test different programs rather than rely on campus mandated reporting requirements to satisfy their duties in this area